Activation of erk1/2 and axogenesis induced by estradiol depend on different calcium pools in male rat hypothalamic neurons in vitro - Cabrera Zapata, Lucas Ezequiel; Cambiasso, María Julia (2023)
Fil: Cabrera Zapata, Lucas Ezequiel. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra; Argentina.